Analysis Impact of Increase in Participants BPJS Class III on Quality of Health Services - Ivan Armawan, (Jurnal Indonesia Sosial Sains, 2021)
Abstract: The type of this research is a quantitative research design case study. Analysis was done on the participants BPJS've been me at the health centre and hospital in the city of Balikpapan. Subjects were Participants of BPJS Health Class III have been using BPJS card class III at the service of health centres and hospitals in the City of Balikpapan. Data collection techniques using a questionnaire with a sample data of 114 people. The results were analyzed using the app statistic SPSS version 22.0. The study results showed that 58% of the Quality of health services in hospitals and community health centres in the City of Balikpapan effect on increasing the number of participants BPJS Health Class III. And variables are the most influential is the Responsiveness or responsiveness officer of 47.2%; this is a positive response so that in the future, the Quality of health services can be improved to be better so that the benefits can be felt directly by the participants of BPJS Health, especially in class III.